2019
DOI: 10.1051/ocl/2019006
|View full text |Cite
|
Sign up to set email alerts
|

A review on newer techniques in extraction of oleaginous flaxseed constituents

Abstract: Flaxseed is the chief oilseed crop that is grown in many regions of the world for medicinal and nutritional purposes. It has been used for oil and fiber since centuries. Flaxseed has an enormous role in functional foods for its nutritional and pharmaceutical values. Among the various components of flaxseed lignans, phenolic acids, proteins and oil are of the main interest. Oil and lignans have prime concentrations in the flaxseed. To study the extraction of these compounds, various extraction methods have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Although the mechanical pressing method is quite popular for flaxseed oil processing, a drawback of this technique is the low extraction recovery of the oil. To improve the yield of extracted oil, many new extraction methods, for example, ultrasound-assisted extraction, microwaveassisted extraction, supercritical CO 2 extraction, subcritical extraction, three-phase partitioning, enzyme-assisted three-phase partitioning etc., have been developed (Kulkarni et al, 2017;Ren et al, 2015;Rombaut et al, 2017;Piva et al, 2018;Sharma et al, 2019;Suri et al, 2020;Szydlowska-Czerniak et al, 2020;Tan et al, 2016).…”
Section: New Extraction Methods For Flaxseed Oilmentioning
confidence: 99%
See 4 more Smart Citations
“…Although the mechanical pressing method is quite popular for flaxseed oil processing, a drawback of this technique is the low extraction recovery of the oil. To improve the yield of extracted oil, many new extraction methods, for example, ultrasound-assisted extraction, microwaveassisted extraction, supercritical CO 2 extraction, subcritical extraction, three-phase partitioning, enzyme-assisted three-phase partitioning etc., have been developed (Kulkarni et al, 2017;Ren et al, 2015;Rombaut et al, 2017;Piva et al, 2018;Sharma et al, 2019;Suri et al, 2020;Szydlowska-Czerniak et al, 2020;Tan et al, 2016).…”
Section: New Extraction Methods For Flaxseed Oilmentioning
confidence: 99%
“…Three-phase partitioning process has been developed to extract flaxseed oil, which is usually performed through adding salt and t-butanol to aqueous extracts (Kulkarni et al, 2017;Sharma et al, 2019). Tan et al (2016) utilized enzyme-assisted three-phase partitioning method to extract flaxseed oil, and showed that the yield of flaxseed oil could reach up to 71.68% under the optimized conditions.…”
Section: New Extraction Methods For Flaxseed Oilmentioning
confidence: 99%
See 3 more Smart Citations